2022
DOI: 10.3389/fpsyg.2022.892551
|View full text |Cite
|
Sign up to set email alerts
|

Board Gender Diversity, Corporate Social Responsibility Disclosure, and Firm’s Green Innovation Performance: Evidence From China

Abstract: The current research investigates the interplay of board gender diversity (BGD), the quality of corporate social responsibility disclosure (CSRD), and the green innovation performance (GIP) of a firm. It examines the moderation effect of the CSRD on the relationship between corporate GIP and BGD. The study inculcates 3,736 firm-year observations of A-share listed Chinese firms from 2010 to 2019. Least square dummy variables method, generalized method of moments, and 2SLS are employed for the analysis of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 75 publications
0
19
0
1
Order By: Relevance
“…The current research on the green innovation of enterprises is mainly carried out from its internal and external influencing factors. In the study of internal influencing factors, Naveed et al [31] took 3736 annual observations of A-share listed companies in China from 2010 to 2019 as samples and found that the gender diversity of the board of directors promotes enterprise green innovation. Wan et al [32] indicated that the management vision and investment vision of enterprise managers are the core supporting factors of green innovation performance.…”
Section: Research On Enterprise Green Innovationmentioning
confidence: 99%
“…The current research on the green innovation of enterprises is mainly carried out from its internal and external influencing factors. In the study of internal influencing factors, Naveed et al [31] took 3736 annual observations of A-share listed companies in China from 2010 to 2019 as samples and found that the gender diversity of the board of directors promotes enterprise green innovation. Wan et al [32] indicated that the management vision and investment vision of enterprise managers are the core supporting factors of green innovation performance.…”
Section: Research On Enterprise Green Innovationmentioning
confidence: 99%
“…The increasing probe into the antecedents and outcomes of GI has lodged to exhume the underpinnings of firms' moot engagement in it. Extant literature has reported various other foundations of GI apart from stakeholders' perspective, including ethical obligations (Walker et al, 2014), competitiveness (Bansal & Roth, 2000), legitimisation and social expectation (Lee et al, 2018), social resilience (Naveed et al, 2022) and upper echelon perspective (Francoeur et al, 2017). These underpinnings premise three categories: Empirical studies in this regard have tested the propositions concerning the BGD-GI relationship and have found inconclusive results (Zaman et al, 2022).…”
mentioning
confidence: 99%
“…BGD is the independent variable that was operationalized through the percent of women on the board (Naveed, Voinea, & Roijakkers, 2022).…”
Section: Independent Variablementioning
confidence: 99%
“…This study focuses on the Chinese market and explores the impact of environmental governance on firms' commitment to environmental issues across China's regions to better understand the driving pressures behind this differentiation. This research addresses the pressing need for further exploration of how subnational contingencies may impact the influence of different stakeholders in the environmental commitment of firms (Naveed, Voinea, & Roijakkers, 2022). It is crucial to investigate the impact of subnational level institutional analysis on the relationship between BGD and CEC in the context of China.…”
Section: Introductionmentioning
confidence: 99%